2020
DOI: 10.1089/aut.2019.0074
|View full text |Cite
|
Sign up to set email alerts
|

Creating Accessible Survey Instruments for Use with Autistic Adults and People with Intellectual Disability: Lessons Learned and Recommendations

Abstract: Despite growing appreciation of the need for research on autism in adulthood, few survey instruments have been validated for use with autistic adults. We conducted an institutional ethnography of two related partnerships that used participatory approaches to conduct research in collaboration with autistic people and people with intellectual disability. In this article, we focus on lessons learned from adapting survey instruments for use in six separate studies. Community partners identified several common prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 53 publications
6
77
0
1
Order By: Relevance
“…Similar to the findings in our study, autistic adults tend to report difficulties with complex language, imprecise response options, lack of autism relevant items, and inappropriate or insensitive language (e.g. Nicolaidis et al 2020 ). Therefore, it will be important to avoid multi-clause questions, include questions about the intensity and frequency of suicidal thoughts without a plan evident, and provide a more concrete alternative to gauge future suicide intent.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the findings in our study, autistic adults tend to report difficulties with complex language, imprecise response options, lack of autism relevant items, and inappropriate or insensitive language (e.g. Nicolaidis et al 2020 ). Therefore, it will be important to avoid multi-clause questions, include questions about the intensity and frequency of suicidal thoughts without a plan evident, and provide a more concrete alternative to gauge future suicide intent.…”
Section: Discussionsupporting
confidence: 88%
“…COSMIN argues that content validity is the most important foundational property on which all other measurement properties rely on -if a tool is not relevant or clear to the target group, then it is unlikely to adequately capture the intended construct in that group. Despite this, few studies conduct extensive work to establish content validity of tools in groups, using rigorous methods such as participatory approaches [19,[60][61] or cognitive interviewing [62]. In contrast, we conducted extensive work to ensure that the adapted SBQ-ASC captured the unique experience of suicidality in autistic and possibly autistic adults, prior to nalising the tool and assessing its measurement properties in autistic, possibly autistic and non-autistic adults.…”
Section: Discussionmentioning
confidence: 99%
“…AASPIRE meets regularly through text-based chat and email. More information on our processes and guidelines can be found in our participatory methods publications [17][18][19][20] Our community partners identified the study topic, helped shape the grant proposal, and identified the key social media documents analyzed. The PI created first drafts of study materials and the full group discussed and edited the final documents.…”
Section: Community-based Participatory Research Approachmentioning
confidence: 99%